THE INFLUENCE OF ENVIRONMENTAL SOCIAL GOVERNANCE (ESG) ON COMPANY VALUE WITH FINANCIAL PERFORMANCE AS A MEDIATION VARIABLE - Pramisti, Aprilia Arifatul; Istiqomah, Dyah Febriantina (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This research was conducted to analyze the relationship between ESG and company value and the role of financial performance variables as mediation between the two. The sample in this research is the energy company sector listed on the Indonesia Stock Exchange (BEI). By implementing good ESG, a company can improve quality, credibility and public trust. Increasing a company's attractiveness also attracts more investors to invest, so that a company can also improve its financial performance. Thus, good financial performance indicates effective ESG practices, so this can increase the company's value for investors. The sample for this research is companies listed on the Indonesian stock exchange in the energy sector consisting of 42 companies with a 2 year period from 2021 to 2022. The statistical tool used is the e-views 12 program with a quantitative approach through the method used for mediation regression analysis multiple. It is known that research shows that ESG influences company value and company financial performance. However, financial performance is not able to directly increase company value, this is proven by the financial performance variable which is proxied by ROA showing less than optimal figures so that it is unable to mediate the relationship between ESG and company value. This research supports the development of the application of ESG practices in energy companies in order to improve the company's credibility and attract more investors in the future.